CORRELATION BETWEEN STUDENTS’ VOCABULARY MASTERY AND THEIR READING COMPREHENSION - Fajar Furqon (Journal of English and Education, 2013)
The paper deals with the correlation between students’ vocabulary mastery and their reading comprehension. Data were collected from 34 second grade students. The test items of reading comprehension and vocabulary mastery were given to the students to measure their level of reading comprehension and vocabulary mastery. The results were compared to find out the correlation between those variables. The findings showed that there was a strong correlation between students’ vocabulary mastery and their reading comprehension. The current study concluded that vocabulary mastery was contributive in helping the students to comprehend the texts. Keywords:Correlation, reading comprehension, vocabulary mastery